Pengaruh Prestasi Kerja terhadap Imbalan Ekstrisik dan Dampaknya pada Kepuasan Kerja (Studi Kasus Pada Karyawan Bagian Pemasaran di Asuransi Jiwa Bumi Asih Jaya Cabang Malang) - Margono Margono (Universitas Negeri Surabaya, 2018)
This research is based on the fact that working satisfaction of the staff is an essential part for an organization. A low working satisfaction will give a bad effect for the organization. That is why the organization leader must be able to increase the working satisfaction of his staff by giving a fair and reasonable extrinsic payment. It should be in assordance with the working performance of the staff and the standard of the minimum regional wage. The purpose of this research is to know the effect of working performance on extrinsic payment and its impact on working satisfaction. The research is case study. The data were taken from 47 responden and all were considered as population. The instrument for collecting the main data was done by distributing questionnaire and the data are measured by using likerd scale. The product Moment Corelation is used to test the validity of the data with the dedree of significance 0,05 while the reliability is test by using Alpa Cronbach technique with degree of significance 0,05. The descriptive analisis an path analysis are used to analyze the data. The researcher used F-Test, T-test, and R-test with the degree of significance the working satisfaction and payment. The result shows that the quality of the staff performance has mostly been midified to meet the companys standard. Most of the staff working performance hared well by their leader. On thye other hand, most of extrinsic payment receveid by the staff has been given sufficient enough. Moreover, its amount is suitable with the staff working performance. The same thing is found out in relation to the staff working satisfaction which is quite good.